2010
DOI: 10.17221/89/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

TaqMan allelic discrimination assay for A1 and A2 alleles of the bovine CSN2 gene

Abstract: Alleles A1 and A2 of the Bos taurus CSN2 gene are the most frequent in a number of dairy cattle breeds. In this study, a new allelic discrimination assay using TaqMan fluorogenic probes was developed to detect single nucleotide substitution characterizing the A1/A2 alleles of the CSN2 gene. The method was validated using DNA samples of known genotypes with different concentrations and the results were compared with those for the commonly used problematic ACRS-PCR. We found the TaqMan method to be more effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…For instance, a study in Denmark indicated a slight superiority of A1 β-casein for Black-and-White breed (0·550 of total β-casein; Bech & Kristiansen, 1990) and Ehrmann (1997) reported that the situation in Germany was similar (A1 0·573 of total β-casein for Red-and-White). More recently a study from Holstein-Friesian cows in India showed that A2 β-casein was the main β-casein variant (A2 0·559, A1 0·441 of total β-casein; Sodhi et al 2012) and this was also the case in a study in the Czech Republic (A2 0·550, A1 0·450; Manga & Dvořák, 2010). Compared with these studies, the frequency of β-casein A1/A2 alleles in the Chinese Holstein is relatively low, perhaps as a result of natural evolution and crossbreeding.…”
Section: Resultsmentioning
confidence: 88%
“…For instance, a study in Denmark indicated a slight superiority of A1 β-casein for Black-and-White breed (0·550 of total β-casein; Bech & Kristiansen, 1990) and Ehrmann (1997) reported that the situation in Germany was similar (A1 0·573 of total β-casein for Red-and-White). More recently a study from Holstein-Friesian cows in India showed that A2 β-casein was the main β-casein variant (A2 0·559, A1 0·441 of total β-casein; Sodhi et al 2012) and this was also the case in a study in the Czech Republic (A2 0·550, A1 0·450; Manga & Dvořák, 2010). Compared with these studies, the frequency of β-casein A1/A2 alleles in the Chinese Holstein is relatively low, perhaps as a result of natural evolution and crossbreeding.…”
Section: Resultsmentioning
confidence: 88%
“…During the last decade, SNP assays have been used to identify species-specific polymorphisms in a wide variety of applications (Best et al 2007;Shastry 2007;Manga & Dvorak 2010). Although other DNA-based techniques (e.g.…”
Section: Number Of Fish In Stomachmentioning
confidence: 99%
“…Kaminski et al (2007) mentioned the frequency of the A1 allele between 0.402 and 0.472 and the A2 allele between 0.470 and 0.598. Additionally, Manga and Dvorak (2010) Bezdicek (2007) stated that its frequency in the population was 0.094 68. Our observed frequency was 0.095 9.…”
Section: Kappa-casein Csn3_ay380228_13165mentioning
confidence: 99%